2015
DOI: 10.3390/ijms16011043
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressure Influences HIF-2 Alpha Expression in Chondrocytes

Abstract: Hypoxia-inducible factor (HIF)-2α is considered to play a major role in the progression of osteoarthritis. Recently, it was reported that pressure amplitude influences HIF-2α expression in murine endothelial cells. We examined whether hydrostatic pressure is involved in expression of HIF-2α in articular chondrocytes. Chondrocytes were cultured and stimulated by inflammation or hydrostatic pressure of 0, 5, 10, or 50 MPa. After stimulation, heat shock protein (HSP) 70, HIF-2α, nuclear factor kappa B (NF-κB), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Finally, COL 10 was detected in loaded specimens (C, lower panel, in green) but in a lower amount in comparison with COL 2, thus confirming that cells were not adopting a hypertrophic phenotype due to the continuous mechanical stimulation provided by daily bioreactor operating. These data are in accordance to literature as compressive stress combined with shear flow allows a higher MSC commitment11333442. Hence, IF staining confirmed the PCR data, providing further important indication of the successful bioreactor-guided chondrogenesis.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, COL 10 was detected in loaded specimens (C, lower panel, in green) but in a lower amount in comparison with COL 2, thus confirming that cells were not adopting a hypertrophic phenotype due to the continuous mechanical stimulation provided by daily bioreactor operating. These data are in accordance to literature as compressive stress combined with shear flow allows a higher MSC commitment11333442. Hence, IF staining confirmed the PCR data, providing further important indication of the successful bioreactor-guided chondrogenesis.…”
Section: Resultssupporting
confidence: 90%
“…Thus, although cells are metabolically active (as confirmed by PCR findings and increased GAG synthesis), they seem to lack the appropriate environment or proper stimuli to produce a structured extracellular matrix within the timeframe of this experiment9. Moreover, by using fibrin glue as cells matrix in a newly developing construct, the bulk of the newly synthesized GAG was released into the culture medium as the pericellular matrix was not sufficiently developed to retain the newly produced GAG323334. Therefore, the MC hydrogel seems to act similarly to fibrin according to obtained and previous results.…”
Section: Resultsmentioning
confidence: 80%
“…Mechanical stress is also directly applied to articular cartilage and bone during treadmill running [ 27 ]. We previously reported that moderate hydrostatic pressure on chondrocytes enhances production of the cartilage matrix, and excessive hydrostatic pressure promotes the expression of proinflammatory cytokines such as IL-6, TNF-α, and a cartilage matrix-degrading enzyme [ 28 , 29 ]. Therefore, we suspected that treadmill running may act as not only a suppressor of pro-inflammatory cytokine production from the synovial membrane, but also a joint protector through mechanical stress applied to the articular cartilage per se, resulting in suppression of joint destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical overload in bovine cartilage disks increases MMP and decreases TIMP expression, and this can be reversed with a VEGFR-2 inhibitor. (49) Mechanical loads are thought to stimulate both hypoxia inducible factor-1a-and -2a (HIF-1 a and HIF-2a)mediated upregulation of VEGF in chondrocytes, (49,109,110) and hypoxia itself is a prime regulator of increased HIFs. (103,108,111,112) Mechanical loading at osteocytes also increases VEGF expression.…”
Section: Introductionmentioning
confidence: 99%